Higher levels of interleukin IL-17 and antigen-specific IL-17 responses in pulmonary sarcoidosis patients with Löfgren's syndrome. (1st October 2014) - Ostadkarampour, M; Eklund, A; Moller, D; Glader, P; Olgart Höglund, C; Lindén, A; Grunewald, J; Wahlström, J
Summary: Sarcoidosis is a granulomatous disorder of unknown aetiology. The presence of Mycobacterium tuberculosis catalase-peroxidase (mKatG) in sarcoidosis tissue has been reported. T helper type 1 (Th1) responses against mKatG have previously been observed. However, little is known about interleukin (IL)-17 and Th17 responses in sarcoidosis. Here, we investigated the levels of IL-17 and frequencies of IL-17-producing cells responding to mKatG in sarcoidosis patients with different prognosis. Peripheral blood and bronchoalveolar lavage (BAL) cells were obtained from sarcoidosis patients with or without Löfgren's syndrome (often associated with spontaneous recovery), and also stratified according to human leucocyte antigen (HLA) type. Cells producing IL-17 and interferon (IFN)-γ after stimulation with mKatG were enumerated by enzyme-linked immunospot (ELISPOT). The level of IL-17 in the BAL fluid of sarcoidosis patients and healthy controls was measured by quantitative immuno-polymerase chain reaction (qIPCR). We also performed flow cytometry and immunohistochemistry for further characterization of IL-17 expression. Patients with Löfgren's syndrome had a higher frequency of IL-17-producing cells responding to mKatG in BAL fluid compared to patients without Löfgren's syndrome ( P < 0·05). The HLA-DR3 + sarcoidosis patients with Löfgren's syndrome (known to have a particularly good prognosis) also had a clearly higher level of IL-17 in BAL fluid compared to healthy controls and sarcoidosis patients without Löfgren's syndrome ( P < 0·01) and ( P < 0·05), respectively. No such difference between patient groups was observed with regard to IFN-γ and not with regard to either cytokine in peripheral blood. These findings suggest that IL-17-producing cells may be a useful biomarker for the prognosis of sarcoidosis and play a role in the spontaneous recovery typical of patients with Löfgren's syndrome.